‮lkhl shlṭnyh‬‎—A New Edition of the Wolfe Golden Amulet in Jewish Palestinian Aramaic - Morgenstern, Matthew 1968- (2022)
The article presents a new edition of the Wolfe Golden Amulet based upon a close examination of new RTI images and its interpretation in light of related Aramaic and Hebrew sources. New readings and translations are presented for many parts of the text.
Keywords: Amulets; Jewish Palestinian Aramaic